Peran Literasi Keuangan dan Literasi Digital dalam Meningkatkan Kinerja UMKM - Bidasari; Sahrir; Goso; Rahmad Solling Hamid (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of this study is to determine the relationship between financial literacy and digital literacy on the performance of MSMEs. This study uses a quantitative approach method through the distribution of online questionnaires. The population in this study is all MSME actors in Luwu Utara Regency, specifically in Masamba District. The sampling technique used is random sampling, namely random sampling based on a predetermined sample. The sample size was taken based on 10 times the calculation of the number of sample measurements and obtained a sample size of 100 samples. The analytical method used is linear regression analysis. The results of this study obtained information that financial literacy and digital literacy have a positive and significant effect on MSME performance.